Descriptive analysis of Finnish equity, bond and money market returns - Peter Nyberg; Mika Vaihekoski (Bank of Finland, 2011)
This paper gathers the longest available historical monthly return series for the Finnish equity, bond and money markets as well as inflation. The series are analysed to calculate the statistical characteristics of the returns investors would have received in these markets. We also survey existing literature concerning the history of these markets and review the main developments to facilitate future research on the long-term development of the Finnish markets. Using a new total return stock market index for Finland in an approach similar to Mehra and Prescott (2003), we find the equity premium for Finland to be 10.14 per cent from 1913 to 2009.
URN:NBN:fi:bof-20140807219
Keywords: 330